Respuestas

2013-07-08T01:14:38+02:00
A. (-4) [(-5) + 3 ]
((-4)*(-5))+((-5)*3)
(20)+(-12)
20-12=8

b.[-8+ (-4)] (-6)
((-8)*(-6))+((-4)*(-6))
(48)+(24)
48+24=72

c.(6)[8+(-2)]
(6*8)+(6*(-2))
(48)+(-12)
48-12=36

d.(+5)[(-7) + (-3)]
(5*(-7))+(5*(-3))
(-35)+(-15)
-35-15=-50

e.(9)[6 + 11]
(9*6)+(9*11)
54+99=153

f. [(-7) + 6](-12)
((-7)*(-12))+(6*(-12))
(84)+(-72)
84-78=12

g.10[(-8) + (-6)]
(10*(-8))+(10*(-6))
(-80)+(-60)
-80-60=-140

h. [(-11) + 3](-5)
((-11)*(-5))+(3*(-5))
(55)+(-15)
55-15=40
men revisa mis preguntas y resuelvelas por favor ok ;)